Antitumor activity of cyclin‐dependent kinase inhibitor alsterpaullone in Epstein‐Barr virus‐associated lymphoproliferative disorders. Issue 1 (11th December 2019) - Watanabe, Takahiro; Sato, Yoshitaka; Masud, H. M. Abdullah Al; Takayama, Masahiro; Matsuda, Hiroki; Hara, Yuya; Yanagi, Yusuke; Yoshida, Masahiro; Goshima, Fumi; Murata, Takayuki; Kimura, Hiroshi
Abstract: Epstein‐Barr virus (EBV) is a well‐established tumor virus that has been implicated in a wide range of immunodeficiency‐associated lymphoproliferative disorders (LPDs). Although rituximab, a CD20 mAb, has proven effective against EBV‐associated LPDs, prolonged use of this drug could lead to resistance due to the selective expansion of CD20 − cells. We have previously shown that cyclin‐dependent kinase (CDK) inhibitors are able to specifically suppress the expression of viral late genes, particularly those encoding structural proteins; however, the therapeutic effect of CDK inhibitors against EBV‐associated LPDs is not clear. In this study, we examined whether CDK inhibitors confer a therapeutic effect against LPDs in vivo. Treatment with alsterpaullone, an inhibitor of the CDK2 complex, resulted in a survival benefit and suppressed tumor invasion in a mouse model of LPDs. Inhibition of CDK efficiently induced G1 cell cycle arrest and apoptosis in EBV‐positive B cells. These results suggest that alsterpaullone suppresses cell cycle progression, resulting in the antitumor effect observed in vivo . Abstract : Epstein‐Barr virus (EBV) is a well‐established tumor virus that has been implicated in a wide range of immunodeficiency‐associated lymphoproliferative disorders (LPDs). In this study, we examined whether cyclin‐dependent kinase (CDK) inhibitors confer a therapeutic effect against LPDs in vivo. Treatment with alsterpaullone, an inhibitor of the CDK2 complex, resulted in a survival benefit and suppressed tumor invasion in a mouse model of LPDs. Inhibition of CDK efficiently induced G1 cell cycle arrest and apoptosis in EBV‐positive B cells.